A statistical analysis of causal factors influencing college student’s willingness to consume digital music - Yu Shan; Fengdie Hu; Yabo Xie; Lixin Bai; Eksiri Niyomsilp (PLoS ONE, 2025)
Determining the causal factors influencing college students’ willingness to consume digital music in China is crucial given the rapid integration of digital technology with the traditional music industry. Chengdu, as a rapidly developing city in China with a thriving youth culture and a significant presence of higher education institutions, provides an ideal setting to explore the factors influencing college students’ willingness to consume digital music. Using a mixed-method approach and a sample of 431 college students from various universities in Chengdu, this research examines the impact of perceived value, behavioral attitude, subjective norms, user participation, user stickiness, and psychological needs on digital music consumption intention. The empirical results show that these factors jointly affect consumption intention, with user stickiness and psychological needs serving as mediators. Specifically, perceived value, behavioral attitude, subjective norms, and user participation have a significant positive impact on consumption intention. These findings provide valuable insights for digital music platforms and the music industry to develop targeted marketing strategies and services tailored to the demands and behaviors of college students in Chengdu.